UMPSA top choice for 5 friends from Sabah to pursue studies in Mechanical Engineering (Petroleum) - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 8 March 2025 – Five friends from Sabah registered together today at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) to begin their studies in the Bachelor of Mechanical Engineering Technology (Petroleum) with Honours at the Faculty of Chemical and Process Engineering Technology (FTKKP).